Antimicrobial resistance in faecal Escherichia coli isolates from farmed red deer and wild small mammals. Detection of a multiresistant E. coli producing extended-spectrum beta-lactamase. (April 2016) - Alonso, C.A.; González-Barrio, D.; Tenorio, Carmen; Ruiz-Fons, F.; Torres, C.
Graphical abstract: Highlights: Although in low rate, AMR bacteria are present in non-selective pressure environments. Multi-resistant ESBL- E. coli can colonize the gut of wild mammals. We report an unusual integron in E. coli carrying multiple antibiotic resistance genes. ST224, associated with multiresistance, is well adapted to clinical and natural settings. Abstract: Eighty-nine Escherichia coli isolates recovered from faeces of red deer and small mammals, cohabiting the same area, were analyzed to determine the prevalence and mechanisms of antimicrobial resistance and molecular typing. Antimicrobial resistance was detected in 6.7% of isolates, with resistances to tetracycline and quinolones being the most common. An E. coli strain carrying bla CTX-M-1 as well as other antibiotic resistant genes included in an unusual class 1 integron ( Intl1 - dfrA16 – bla PSE-1 - aadA2 - cmlA1 - aadA1 - qacH -IS 440 - sul3 - orf1 - mef (B)Δ-IS 26) was isolated from a deer. The bla CTX-M-1 gene was transferred by conjugation and transconjugants also acquired an IncN plasmid. This strain was typed as ST224, which seems to be well adapted to both clinical and environmental settings. The phylogenetic distribution of the 89 strains varied depending on the animal host. This work reveals low antimicrobial resistance levels among faecal E. coli from wild mammals, which reflects a lower selective pressure affecting these bacteria, compared to livestock. However, it is remarkable the detection of a multi-resistant ESBL- E. coli with an integron carrying clinically relevant antibiotic-resistance genes, which can contribute to the dissemination of resistance determinants among different ecosystems.